Production de l'hétéronormativité. - Fidolini, Vulca, author.
1 online resource.
Keywords: "Drawing on an ethnographic study on young Moroccan immigrants in Europe (France and Italy), this book analyses the hegemonic power of heteronormativity and its plural expressions. It tries to give an answer to the following main questions: How the normative power of heterosexuality is socially constructed among men? How and why heterosexuality is interpreted as the socially "appropriate" norm to be recognized as a "true" man by other men? Attention is focused on those people who use heteronormativity in order to produce and reproduce heterosexual identifications through performing hegemonic masculinities. The objective is to deconstruct the "normality" of heterosexuality and the ways through which it is commonly used as a normative reference to talk about sexual life as well as to build masculinities, especially within homosocial relationships. An enlightening book consisting of a rich empirical material and theoretical analysis, this volume will appeal to undergraduate and postgraduate students, as well as postdoctoral researchers who are interested in fields such as Sociology, Anthropology and Gender Studies"--